An age of consent : press representations of endemic sexual abuse of young girls by Pitcairn Island men : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Women's Studies at Massey University - Robison, Vivien Ruth (Massey University, 2004)
This thesis is an analysis of press representations of Pitcairn Island women's complaints of child sexual abuse by the island's men. Press constructions of the case provide an opportunity to analyse how western society represents the alleged endemic sexual abuse of young Pitcairn girls by family and family friends. A database of 93 press reports draws on British, New Zealand and Australian newspapers and includes reports from the first mention of criminal charges in March 2001 until most of the charges had been laid against offenders in July 2003. A dual research method combines a chronological content analysis of the whole database with a detailed discourse analysis of two reports to examine how discursive strategies categorised, minimised and normalised the Pitcairn crimes. Representations of familial/familiar sexual abuse in the Pitcairn case do not fit with stereotypical constructions of child sexual abuse as 'psychopathic' violence and 'paedophilic' stranger-danger. This thesis shows that the press diffused the issue as one of cultural, rather than sexual, consent in order not to have to explain the contradiction-in-terms that is endemic familial/familiar sexual abuse of young girls in a respectable community. Cultural relativism undermines the credibility of the women complainants. The thesis argument is that the press finds the issue of familial/familiar sexual abuse of girls younger than 12 years of age. which is the most prevalent category of sexual abuse in society, difficult to represent.
Keywords: Pitcairn Island; Age of consent; Child sexual abuse -- Press coverage